The ten commandments of lean six sigma : a guide for practitioners - Antony, Jiju; Sunder, Vijaya M.; Laux, Chad; Cudney, Elizabeth (Emerald Publishing Limited, 2019)
Presented from the perspective of practitioners, researchers and academics, The Ten Commandments of Lean Six Sigma serves as a practical guide for senior managers and executives who want to achieve operational and service excellence in various manufacturing, service and public sector organization.